2020
DOI: 10.3390/ijerph17062110
|View full text |Cite
|
Sign up to set email alerts
|

Boda Bodas and Road Traffic Injuries in Uganda: An Overview of Traffic Safety Trends from 2009 to 2017

Abstract: Introduction: Road traffic injuries (RTIs) are an important contributor to the morbidity and mortality of developing countries. In Uganda, motorcycle taxis, known as boda bodas, are responsible for a growing proportion of RTIs. This study seeks to evaluate and comment on traffic safety trends from the past decade. Methods: Traffic reports from the Ugandan police force (2009 to 2017) were analyzed for RTI characteristics. Furthermore, one month of casualty ward data in 2015 and 2018 was collected from the Mulag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…For two-thirds of the RTC, the counterparts in the rural setting were riding motorcycles while the same share accounts for cars in Urban Hospital 1 ( p < 0.001). Some differences could be explainable by infrastructural differences such as paving and sidewalks as well as traffic density, vehicles and (especially in rural areas) speeding [ 10 ]. Consistent with previous research findings, this study identified both motorcyclists and pedestrians as the most vulnerable groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For two-thirds of the RTC, the counterparts in the rural setting were riding motorcycles while the same share accounts for cars in Urban Hospital 1 ( p < 0.001). Some differences could be explainable by infrastructural differences such as paving and sidewalks as well as traffic density, vehicles and (especially in rural areas) speeding [ 10 ]. Consistent with previous research findings, this study identified both motorcyclists and pedestrians as the most vulnerable groups.…”
Section: Resultsmentioning
confidence: 99%
“…In regards of gender, males dominated those affected by injuries obtained during crashes in all modes of transport: men account for 94% of bicycle injuries and 75% of motorcycle injuries and showed equal risk for RTI regardless of an active or passive traffic role (pedestrian, driver or passenger). Females are almost at the same risk of being injured as a pedestrian and as a motorcycle-passenger, which is a vehicle they almost never actively drive [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly 15% of incidents were suspected or confirmed to involve substance intoxication. The substantial rates of injury associated with boda bodas in Uganda are well-documented, due in part to the country’s poorly enforced speed limits and traffic safety laws [ 15 ]. Only 15% of patients injured on the road in Soroti were pedestrians–a stark contrast from other studies in Uganda and neighboring countries, perhaps attributable to the rural nature of the hospital’s catchment area [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%